2020
DOI: 10.1021/acs.macromol.0c00745
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Absorptive and Emissive Poly(p-phenylene vinylene) Derivative Containing Azobenzene–Boron Complexes

Abstract: Poly­(p-phenylene vinylene) (PPV) is known to be a typical π-conjugated polymer and used as a commodity platform for constructing optoelectronic organic devices because of superior optical and material properties. PPV derivatives generally show a large degree of light absorption and intense emission in the visible region; meanwhile, very few examples have been reported to offer near-infrared (NIR) absorptive and emissive PPV derivatives. In this study, we designed and synthesized a novel PPV derivative, named … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 74 publications
2
47
0
Order By: Relevance
“…[28][29][30] As examples, we discovered cubic silica and boron cluster compounds named polyhedral oligomeric silsesquioxane (POSS) [31,32] and ocarborane, [33,34] respectively, have been applicable to main scaffolds for creating functional materials showing superior luminescence behaviors with high durability or stimuli-responsiveness. We recently reported the series of solid-state luminescent complexes and polymers containing boron-fused azomethine (À C=NÀ ) [35][36][37][38][39] and azo (À N=NÀ ) [40][41][42][43][44] complexes with the tridentate ligands, o-salicylideneaminophenol or 2,2'-dihydroxyazobenzne scaffold, respectively. [45] These materials showed intense emission in the condensed state, and highlyefficient polymer film emission [38] and near-infrared (NIR) absorptive and emissive characteristics [40][41][42]44] were obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] As examples, we discovered cubic silica and boron cluster compounds named polyhedral oligomeric silsesquioxane (POSS) [31,32] and ocarborane, [33,34] respectively, have been applicable to main scaffolds for creating functional materials showing superior luminescence behaviors with high durability or stimuli-responsiveness. We recently reported the series of solid-state luminescent complexes and polymers containing boron-fused azomethine (À C=NÀ ) [35][36][37][38][39] and azo (À N=NÀ ) [40][41][42][43][44] complexes with the tridentate ligands, o-salicylideneaminophenol or 2,2'-dihydroxyazobenzne scaffold, respectively. [45] These materials showed intense emission in the condensed state, and highlyefficient polymer film emission [38] and near-infrared (NIR) absorptive and emissive characteristics [40][41][42]44] were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the series of solid-state luminescent complexes and polymers containing boron-fused azomethine (À C=NÀ ) [35][36][37][38][39] and azo (À N=NÀ ) [40][41][42][43][44] complexes with the tridentate ligands, o-salicylideneaminophenol or 2,2'-dihydroxyazobenzne scaffold, respectively. [45] These materials showed intense emission in the condensed state, and highlyefficient polymer film emission [38] and near-infrared (NIR) absorptive and emissive characteristics [40][41][42]44] were obtained. It should be emphasized that unique environment-sensitive luminescent properties, such as aggregation-induced emission (AIE), [46,47] crystallization-induced emission enhancement (CIEE), [48] in which enhanced emission can be observed only in aggregation and crystal, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the PPV scaffold usually works as a donor moiety, [64] the opposite electron‐accepting properties of the PAM and PAZ scaffold are of interest and useful for constructing functional π‐conjugated polymers. Furthermore, we found that construction of the PPV‐like structure with alternating copolymerization between BAz and vinylene units achieved NIR absorption and emission although there were no electron‐donating units [65] . Although the wavelengths of absorption and emission of PPV are limitedly from blue to orange region, [66,67] narrow energy gap between FMOs in ground and excited states can be achieved by employing the PAM and PAZ structures.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, an O–B←N‐embedded polymer (80b) analogous to poly(p‐phenylene vinylene) with NIR absorption and were reported. [ 133 ] In comparison with the B‐free polymer 80a, B‐complexed 80b showed significantly a bathochromic absorption maximum (510 vs. 702 nm), lowered HOMO (−5.30 vs. −5.38 eV) and LUMO (−3.23 vs. −3.98 eV), and narrowed bandgap (2.07 vs. 1.60 eV). Moreover, nonfluorescence was observed for 80a, whereas NIR luminescence was found for B‐complexed 80b.…”
Section: B←n‐bridged Conjugated Unitsmentioning
confidence: 99%